THE PRESERVATION OF CULTURAL HERITAGE IN THE CONTEXT OF TOURISM: THE ROLE OF SOCIAL STUDIES EDUCATION IN TÜRKIYE - Kocoglu, Erol; Eguz, Sule; Avcu, Kubra Melis (Scientia Socialis, 2024)
T & uuml;rkiye is a region that bears the traces of many different civilizations from the past to the present. This diversity has endowed the country's culture with a deep and rich dimension. This study examines the role of social studies education in the preservation of cultural heritage in Turkey and its relationship with tourism. The aim of the research is to reveal the potential contributions of social studies education to the sustainability of cultural heritage and the development of tourism by evaluating its impact on students. Conducted within the framework of a qualitative research design, the study involved a comprehensive literature review and an analysis of the 2005 and 2018 social studies curricula for grades 4, 5, 6, and 7. The findings indicate that social studies education provides students with significant awareness regarding the preservation of cultural heritage in Turkey and its integration with tourism. Furthermore, this research emphasizes the educational role of social studies education in the context ofpreserving cultural heritage and the sustainability of tourism. These findings may contribute to shaping educational policies in Turkey and other countries in this direction.
Keywords: social studies education; culture and heritage; cultural heritage and tourism; Turkeys' cultural heritage; preservation of cultural heritage